Day 1 Mon, October 15, 2018 2018
DOI: 10.2118/191679-18rptc-ms
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Forecasting and Evaluation of Reservoir Properties Under Conditions of Its Development Using Hydraulic Fracturing Technology

Abstract: Development of well completion and reservoir stimulation technologies has fuzzified the well-established concepts that have been commonly used to identify and estimate productive natural reservoirs. As multi-stage hydraulic fracturing (MSHFC) is broadly applied, the petrophysical criteria in horizontal wells based on the definition of reservoir bottom interface turn out to be inefficient. This may be exemplified by quite a large-scale development of hard-to-recover oil limited to low-permeable rock ("tight oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Al-Ghazal [36] analyzed the practical application data of the multistage fracturing of horizontal wells in a Saudi Arabia tight gas field and revealed that borehole trajectory, reservoir parameters, and completion design are important factors affecting single-well productivity. Alekseev [37] divided the factors affecting the productivity of horizontal wells into three categories, reservoir quality, drilling quality, and completion quality, pointing out that the fracturing technologies differ significantly in parameters and processes; thus, their stimulation effects vary greatly from well to well under the combined influence of reservoir and drilling factors. Chodzicki's [38] results from over 120 wells in the Spearfish low-perm sandstone/siltstone formation, Southwest Manitoba, showed great production results from the application of horizontal well and multistage fracturing techniques, but individual fractured horizontal wells also yield variable results, making it difficult to correlate any strong trends that related initial production rates and estimated ultimate reserves to fracture size, number of stages, or total proppant.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Ghazal [36] analyzed the practical application data of the multistage fracturing of horizontal wells in a Saudi Arabia tight gas field and revealed that borehole trajectory, reservoir parameters, and completion design are important factors affecting single-well productivity. Alekseev [37] divided the factors affecting the productivity of horizontal wells into three categories, reservoir quality, drilling quality, and completion quality, pointing out that the fracturing technologies differ significantly in parameters and processes; thus, their stimulation effects vary greatly from well to well under the combined influence of reservoir and drilling factors. Chodzicki's [38] results from over 120 wells in the Spearfish low-perm sandstone/siltstone formation, Southwest Manitoba, showed great production results from the application of horizontal well and multistage fracturing techniques, but individual fractured horizontal wells also yield variable results, making it difficult to correlate any strong trends that related initial production rates and estimated ultimate reserves to fracture size, number of stages, or total proppant.…”
Section: Introductionmentioning
confidence: 99%